Trials based on specific fracture configuration and surgical procedures likely to be more relevant for decision making in the management of fractures of the proximal humerus: Findings of a meta-analysis. Issue 10 (October 2016) - Sabharwal, S.; Patel, N. K.; Griffiths, D.; Athanasiou, T.; Gupte, C. M.; Reilly, P.
Abstract : Objectives: The objective of this study was to perform a meta-analysis of all randomised controlled trials (RCTs) comparing surgical and non-surgical management of fractures of the proximal humerus, and to determine whether further analyses based on complexity of fracture, or the type of surgical intervention, produced disparate findings on patient outcomes. Methods: A systematic review of the literature was performed identifying all RCTs that compared surgical and non-surgical management of fractures of the proximal humerus. Meta-analysis of clinical outcomes was performed where possible. Subgroup analysis based on the type of fracture, and a sensitivity analysis based on the type of surgical intervention, were also performed. Results: Seven studies including 528 patients were included. The overall meta-analysis found that there was no difference in clinical outcomes. However, subgroup and sensitivity analyses found improved patient outcomes for more complex fractures managed surgically. Four-part fractures that underwent surgery had improved long-term health utility scores (mean difference, MD 95% CI 0.04 to 0.28; p = 0.007). They were also less likely to result in osteoarthritis, osteonecrosis and non/malunion (OR 7.38, 95% CI 1.97 to 27.60; p = 0.003). Another significant subgroup finding was that secondary surgery was more common for patients that underwent internal fixation compared with conservative management within the studies with predominantly three-part fractures (OR 0.15, 95% CI 0.04 to 0.63; p = 0.009). Conclusion: This meta-analysis has demonstrated that differences in the type of fracture and surgical treatment result in outcomes that are distinct from those generated from analysis of all types of fracture and surgical treatments grouped together. This has important implications for clinical decision making and should highlight the need for future trials to adopt more specific inclusion criteria. Cite this article: S. Sabharwal, N. K. Patel, D. Griffiths, T. Athanasiou, C. M. Gupte, P. Reilly. Trials based on specific fracture configuration and surgical procedures likely to be more relevant for decision making in the management of fractures of the proximal humerus: Findings of a meta-analysis Bone Joint Res 2016;5:470–480. DOI: 10.1302/2046-3758.510.2000638.